ChemInform Abstract: A General Metal Free Approach to α‐Ketoamides via Oxidative Amidation—Diketonization of Terminal Alkynes. Issue 3 (January 2015) - Deshidi, Ramesh; Kumar, Manjeet; Devari, Shekaraiah; Shah, Bhahwal Ali
Abstract In the presence of trimethylsilyl triflate and catalytic amounts of iodine, the first metal free oxidative amidation—diketonization of terminal alkynes leads to a wide variety of α‐ketoamides.